Cardiovascular morbidity in the military personnel - I. N. Stupakov; V. I. Gerber (Кардиоваскулярная терапия и профилактика)
Aim. To study cardiovascular morbidity, temporary disability, medical care organization in the military personnel, observed by the medical service of Serpukhov Institute for Rocket Forces. Material and methods. A complex of social and hygienic methods was used: registry data selection, expert assessment of medical documentation, sociological survey (medical staff interview), and statistical analysis. Results. In various age and professional profile groups of the military personnel, prevalence and structure of morbidity and temporary disability were not homogenous. Medical service organization features influenced temporary disability and morbidity levels. Conclusion. To optimize diagnostics and treatment process, it is necessary to develop Russian guidelines on diagnostics and management of patients with atypical or mildly manifested cardiovascular disease, whose working specialty requires initial and continuous professional selection.